2005
DOI: 10.1055/s-2005-869906
|View full text |Cite
|
Sign up to set email alerts
|

A New and Convenient Method of Generating Alkyl Isocyanates from Alcohols­, Thiols and Trimethylsilyl Ethers Using Triphenylphosphine/2,3-Dichloro-5,6-dicyanobenzoquinone/Bu4NOCN

Abstract: Alkyl isocyanates are prepared in good to excellent yields by treatment of alcohols, thiols and trimethylsilyl ethers with triphenylphosphine/2,3-dichloro-5,6-dicyanobenzoquinone/ Bu 4 NOCN in acetonitrile. This method is highly selective for conversion of primary alcohols to alkyl isocyanates in the presence of secondary and tertiary alcohols, thiols and trimethysilyl ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…We found that tetrabutylammonium cyanate was a good source for the amine functionality. Alcohol 11 was treated with Bu 4 NOCN/PPh 3 /DDQ to give an isocyanate intermediate,18 which was subsequently treated with t BuOH to give carbamate 15 in 78 % yield (Scheme ). A Pd‐catalyzed coupling reaction with diethyl phosphite was carried out to form phosphonate 17 b , and subsequently tamiphosphor ( 3 ) was synthesized by concurrent removal of the Boc and the ethyl groups with TMSBr under mild reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…We found that tetrabutylammonium cyanate was a good source for the amine functionality. Alcohol 11 was treated with Bu 4 NOCN/PPh 3 /DDQ to give an isocyanate intermediate,18 which was subsequently treated with t BuOH to give carbamate 15 in 78 % yield (Scheme ). A Pd‐catalyzed coupling reaction with diethyl phosphite was carried out to form phosphonate 17 b , and subsequently tamiphosphor ( 3 ) was synthesized by concurrent removal of the Boc and the ethyl groups with TMSBr under mild reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, aromatic isothiocyanates can be introduced from acyl azides or hydroxamic acids via a Curtius or Lossen rearrangement, respectively. Furthermore, Akhlaghinia has reported the successful synthesis of alkyl isothiocyanates from alcohols, thiols and trimethylsilyl ethers using triphenylphosphine, 2,3‐dichloro‐5,6‐dicyanobenzoquinone and Bu 4 NOCN under mild reaction conditions …”
Section: The Design Of Irreversible Probesmentioning
confidence: 99%
“…ChemMedChem 2016ChemMedChem , 11,1488ChemMedChem -1498 www.chemmedchem.org dichloro-5,6-dicyanobenzoquinone and Bu 4 NOCN under mild reactionconditions. [44] Disulfides and thiocyanates form covalent SÀSb onds with cysteinea mino acid residues of ar eceptor,b ut when treated with areducing agentssuch as b-mercaptoethanol( BME) or dithiothreitol (DTT) theseb onds are reversible. Ad esirable property of these chemoreactive groups is their exquisite selectivity for the cysteinea mino acid residue restricting the probe to bind to am inimal number of positions within the receptor.D isulfides groups that are frequentlye mployed as parto fi rreversible probesi nclude 2-aminoethan-1-thiol, thiopyridones and derivatives thereof.T he selection of an aromatic disulfide or thiocyanate group is potentially desirable for practical reasons such as the detection with UV light where the pharmacophore doesn'tp ossess such ac hromophore (e.g.,f or the purposeo f chromatography and LC-MS).…”
Section: -Aminoethane-1-thiols [58]mentioning
confidence: 99%
“…In continuation of our search new methods of functional group transformations (Iranpoor et al, 2004a(Iranpoor et al, , 2004b(Iranpoor et al, , 2004c(Iranpoor et al, , 2005Akhlaghinia, 2004Akhlaghinia, , 2005aAkhlaghinia, , 2005bAkhlaghinia & Pourali, 2004;Akhlaghinia & Samiei, 2009;Akhlaghinia & Rouhi-Sadabad 2013;Rouhi-Sadabad & Akhlaghinia, 2014;Kiani et al, 2014), a direct, mild and efficient procedure for the synthesis of various symmetrical acid anhydrides from carboxylic acids using the prepared mixed reagent is reported here.…”
Section: Introductionmentioning
confidence: 96%